Proceedings of the 9th International Conference for Science Educators and Teachers (ICSET 2017) 2017
DOI: 10.2991/icset-17.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

Teacher's Attitude and Peer Acceptance to Children with Special Needs in Inclusive Primary Schools

Abstract: The success of inclusion of children with special needs in inclusive schools largely depends on teachers' attitudes towards students with special needs and their knowledge on how to properly educate them. Regular teachers have different views about the inclusion of students with special needs. The type and level of the children's disabilities affect teachers' willingness to accommodate students with special needs and effective classroom management. The research used descriptive survey method to know the attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…It could be the experience of the teacher that makes them to be more understanding and can follow up the learning outcome with intervention, such as advising students to attend tutoring outside the school. This is in line with Marlina (2017) who suggests that teachers' teaching experiences are related to their attitudes. This finding in line with Ekperi et al (2019) and also Abudu & Gbadamosi (2014).…”
Section: Discussionsupporting
confidence: 90%
“…It could be the experience of the teacher that makes them to be more understanding and can follow up the learning outcome with intervention, such as advising students to attend tutoring outside the school. This is in line with Marlina (2017) who suggests that teachers' teaching experiences are related to their attitudes. This finding in line with Ekperi et al (2019) and also Abudu & Gbadamosi (2014).…”
Section: Discussionsupporting
confidence: 90%
“…Other peers commented on their friendship with this child with a learning disability as a representation of social inclusion and belonging. In contrast, previous research focused on levels of peer acceptance in Indonesia found overwhelmingly negative findings for peer acceptance (Marlina, 2017). For the primary students with learning disabilities, they viewed the teachers who supported students (Good teacher) and a sense of belonging in the wider community (Funny market friends) for their representation of social inclusion, belonging and community.…”
Section: Primary School: Inclusive Charactersmentioning
confidence: 81%
“…For the primary students with learning disabilities, they viewed the teachers who supported students (Good teacher) and a sense of belonging in the wider community (Funny market friends) for their representation of social inclusion, belonging and community. The photovoice project was purposefully conducted in schools specifically espousing the values of inclusive education, and the representations of social inclusion by the primary students without disabilities align with findings from Indonesian research on teachers' attitudes about inclusive education impacts on peer acceptance of students with disabilities (Marlina, 2017).…”
Section: Primary School: Inclusive Charactersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fenomena ini berdampak banyak ABK yang sulit mengikuti pembelajaran, antara lain indikator pembelajaran yang terlalu tinggi, materi terlalu sulit, media pembelajaran yang tidak sesuai dengan jenis disabilitas yang disandang, dan evaluasi hasil belajar yang tidak sesuai dengan kemampuan yang dimiliki. Marlina (2017) dan De Boer et al (2011) juga menyatakan kondisi tersebut menjadi lebih sulit dengan adanya sikap guru yang negatif terhadap kebutuhan pembelajaran ABK, mulai dari persiapan pembelajaran sampai pada evaluasi pembelajaran.…”
Section: Pendahuluanunclassified